Find {x,y} in NN such that (1-sqrt(2)+sqrt(3))/(1+sqrt(2)-sqrt(3))=(sqrt(x)+sqrt(y))/2?
1 Answer
Explanation:
The difference of squares identity can be written:
a^2-b^2=(a-b)(a+b)
Use this a couple of times to find:
(1-sqrt(2)+sqrt(3))/(1+sqrt(2)-sqrt(3)) = ((1-sqrt(2)+sqrt(3))(1+sqrt(2)+sqrt(3)))/((1+sqrt(2)-sqrt(3))(1+sqrt(2)+sqrt(3))
color(white)((1-sqrt(2)+sqrt(3))/(1+sqrt(2)-sqrt(3))) = (((1+sqrt(3))-sqrt(2))((1+sqrt(3))+sqrt(2)))/(((1+sqrt(2))-sqrt(3))((1+sqrt(2))+sqrt(3))
color(white)((1-sqrt(2)+sqrt(3))/(1+sqrt(2)-sqrt(3))) = ((1+sqrt(3))^2-(sqrt(2))^2)/((1+sqrt(2))^2-(sqrt(3))^2)
color(white)((1-sqrt(2)+sqrt(3))/(1+sqrt(2)-sqrt(3))) = (1+2sqrt(3)+3-2)/(1+2sqrt(2)+2-3)
color(white)((1-sqrt(2)+sqrt(3))/(1+sqrt(2)-sqrt(3))) = (2+2sqrt(3))/(2sqrt(2))
color(white)((1-sqrt(2)+sqrt(3))/(1+sqrt(2)-sqrt(3))) = (sqrt(2)+sqrt(2)sqrt(3))/2
color(white)((1-sqrt(2)+sqrt(3))/(1+sqrt(2)-sqrt(3))) = (sqrt(2)+sqrt(6))/2
So